2005
DOI: 10.1080/02699050400002363
|View full text |Cite
|
Sign up to set email alerts
|

A randomized control trial to evaluate a paging system for people with traumatic brain injury

Abstract: Although memory problems following acquired brain damage are common, some people are able to compensate for these problems through external aids. It was recently demonstrated that a paging system could reduce the everyday memory and planning problems for people with non-progressive brain injury. The 143 patients who participated in the study comprised several diagnostic groups. This paper reports on the sub-group of people with TBI (n=63). This sub-group was part of the larger sample of 143 already published i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
49
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(51 citation statements)
references
References 4 publications
2
49
0
Order By: Relevance
“…Wilson et al conducted a randomised controlled trial asking a group of 63 patients with memory problems what specific reminders they would find helpful and pagers improved task achievement from 47% to 72%. 9 It is difficult to comment on the cost effectiveness of such a system. As yet no cost-effectiveness studies have been published in this area.…”
Section: Will My Response Be Kept Confidential?mentioning
confidence: 99%
“…Wilson et al conducted a randomised controlled trial asking a group of 63 patients with memory problems what specific reminders they would find helpful and pagers improved task achievement from 47% to 72%. 9 It is difficult to comment on the cost effectiveness of such a system. As yet no cost-effectiveness studies have been published in this area.…”
Section: Will My Response Be Kept Confidential?mentioning
confidence: 99%
“…Both low-tech (paper) and high-tech methods (computers, cell phones) have been shown to be effective for improving memory [36]. Pagers, personal data assistants, computers, smart phones, and accompanying applications are all highly effective memory prostheses for the person with TBI, and these devices can be individually tailored to his or her needs [37]. While the steps to use these devices must be carefully trained and practiced, a memory log with a calendar, schedule, and important telephone numbers or e-mail addresses can be an effective, low-tech, lowcost intervention [36].…”
Section: Cognitive Deficitsmentioning
confidence: 99%
“…In addition they often have multiple functions and applications that can support memory, such as calendars and voice recorders [1,4]. A number of studies have shown that electronic compensatory memory aids, such as pagers [12,13], mobile phones [14,15], PDAs [1,10,16,17] and smartphones [18,19,20] can be effective in supporting prospective memory in adults with brain injury, by helping them to remember and complete everyday tasks. A recent systematic review also concluded that external assistive devices reduce forgetfulness in adults after traumatic brain injury (TBI) or stroke [21].…”
Section: Introductionmentioning
confidence: 99%
“…Smartphones have become increasingly popular in memory rehabilitation because they have many functions and applications that can help people with memory impairment, for example calendars, alarms, to-do lists, texts and voice recorders [1,5]. Additionally, many children and adolescents already use smartphones, with 62% of [12][13][14][15] year olds owning a smartphone in the UK [23]. Thus, for children and adolescents, smartphones could be viewed as desirable assistive devices as they are popular, inconspicuous and do not highlight their deficits to others [5,18,22].…”
Section: Introductionmentioning
confidence: 99%